Analisis faktor risiko terjadinya phlebitis di RSUD Puri Husada Tembilahan - Siti Rusnawati; Hafni Bachtiar; Deswita Deswita (Universitas Batanghari Jambi, 2020)
Phlebitis is one of the standard indicators of hospital's minimum service with the dimension of patient safety quality. Risk factors for phlebitis include disease, intravenous catheter size, distance insertion place with joints, type of fluid, technique disinfection, dressing techniques and long infusion attached. The research aims to analyse the risk factors of phlebitis. The methods used were observational crossectional analytic conducted in Puri Husada Tembilahan HOSPITAL against 97 patients. The results showed that the factors related to the occurrence of phlebitis is the distance of insertion place with the joints, types of liquids, techniques of disinfection, technique dressings, and prolonged infusion is attached, while the disease factors and the size of the catheter intravenously unrelated to the occurrence of phlebitis. The most dominant factor is related to Phlebitis is disinfection technique (OR = 4.567). The results of this research can be information for nurses in the prevention of phlebitis by conducting disinfection and dressing with sterile technique during the installation of infusion, monitor drip infusion according to therapy, insertion with Distance > 3.5 cm from the joints, and replacing the place of insertion in the patient's attached infusion > 72 hours.